2011
DOI: 10.1007/s10997-011-9179-0
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of voluntary executive stock option disclosure in Brazil

Abstract: This study investigates whether the governance attributes of Brazilian companies are associated with voluntary executive stock option (ESO) disclosure. Results show that Brazilian companies voluntarily disclose very little about their ESO plans, and that board size, presence of a compensation committee, and auditing by a Big 4 firm are significantly related to the degree of voluntary ESO disclosure. We also show that family-controlled companies in Brazil are associated with low voluntary ESO disclosure. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 41 publications
3
28
0
1
Order By: Relevance
“…These injunction firms, which represent approximately 30% of total market value traded on the Bovespa, represents our group of interest. Recent research finds that Brazilian firms remain relatively opaque thanks to the protection of the court injunction (Schiehll et al., ). Appendix B provides a list of the companies taking advantage of the injunction.…”
Section: Background and Hypotheses Developmentmentioning
confidence: 99%
“…These injunction firms, which represent approximately 30% of total market value traded on the Bovespa, represents our group of interest. Recent research finds that Brazilian firms remain relatively opaque thanks to the protection of the court injunction (Schiehll et al., ). Appendix B provides a list of the companies taking advantage of the injunction.…”
Section: Background and Hypotheses Developmentmentioning
confidence: 99%
“…Such firms are considered to be external corporate governance mechanisms that oversee management activities through the firm's financial performance and disclosures (Kang & Yoo, 2012). Evidence points to the fact that large-sized audit firms (big 4) adopt superior auditing performance standards compared to their small audit counterparts (Schiehll, Terra, & Victor, 2013). Hence, large-sized audit firms are expected to have auditors that are experienced, trained and qualified (Barako et al, 2006).…”
Section: Proportion Of Independent Directors and Voluntary Corporate mentioning
confidence: 99%
“…Pinto and Leal [49] showed that in another emerging market setting like Brazil, family controlled firms tend to pay more to their CEOs and board members when controlling shareholders or their relatives act as directors. Schiehll et al [50] assert that family controlled firms in Brazil also tend not to voluntarily disclose their executive stock options plans.…”
Section: Literature Reviewmentioning
confidence: 99%